2017
DOI: 10.1093/ilar/ilx020
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Ecological Framework for Assessing Reservoirs of Vector-Borne Pathogens: Wildlife Reservoirs of Trypanosoma cruzi across the Southern United States

Abstract: Wildlife species are critical for both feeding vectors and serving as reservoirs of zoonotic vector-borne pathogens. Transmission pathways leading to disease in humans or other target taxa might be better understood and managed given a complete understanding of the relative importance of different reservoir species in nature. Using the conceptual framework of “reservoir potential,” which considers elements of both reservoir competence and vector-host contact, we review the wildlife reservoirs of Trypanosoma cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 94 publications
1
56
2
Order By: Relevance
“…Recognition of the associations between parasite DTU and reservoir host species may have important implications for public or veterinary health (Bern et al 2011 ; Jansen et al 2017 ; Hodo and Hamer 2017 ). We found that NHPs were infected almost equally with both TcI and TcIV, whereas the small numbers of raccoons and opossums exclusively harbored TcIV and TcI, respectively—host associations that have been previously shown (Bern et al 2011 ; Roellig et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recognition of the associations between parasite DTU and reservoir host species may have important implications for public or veterinary health (Bern et al 2011 ; Jansen et al 2017 ; Hodo and Hamer 2017 ). We found that NHPs were infected almost equally with both TcI and TcIV, whereas the small numbers of raccoons and opossums exclusively harbored TcIV and TcI, respectively—host associations that have been previously shown (Bern et al 2011 ; Roellig et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…in the USA (Packchanian 1942 ; Charles et al 2012 ), and several studies have reported T. cruzi infection in other species of rodents (Burkholder et al 1980 ; Navin et al 1985 ; Charles et al 2012 ; Herrera et al 2015 ; Aleman et al 2017 ). T. cruzi transmission cycles are characterized by regional heterogeneity, and the important reservoirs likely differ across geographical areas (Hodo and Hamer 2017 ). Because the mammal traps were not placed randomly or systematically along transects, the species and numbers of mammals captured are not necessarily reflective of the entire population structure of the wildlife community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although triatomines found in the United States are generally considered sylvatic, these vectors are regularly encountered in and around human dwellings (Kjos et al, 2008;Wozniak et al, 2015;Curtis-Robles et al, 2018b). Wildlife and domestic canines are infected with T. cruzi throughout Texas and across the southern United States (Beard et al, 2003;Kjos et al, 2008;Brown et al, 2010;Curtis-Robles et al, 2017;Hodo and Hamer, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…is higher than we expected as these species tend to be thought of as minor hosts for Triatominae or are primarily associated only with certain species [42]. This discrepancy may reflect that these hosts are not known to be able to harbor the T. cruzi pathogen [59,60] is that oral transmission in the sylvatic cycle may be the primary mechanism of parasite spread [62] and some insectivorous mammals often have a higher prevalence of the disease [63]. It has been reported that even T. cruzi-infected vertebrates eaten as prey can be infective [64] and it appears that Chagas disease can "bioaccumulate" in predators including highly carnivorous top predators (e.g., ocelots), that are nocturnal without permanent dens and are thus unlikely to be exposed to feeding Triatominae [65].…”
Section: Introductionmentioning
confidence: 69%